TRANSNATIONAL RELIGIOUS ACTOR AND MULTI-TRACK DIPLOMACY: A CASE STUDY FROM THE SPECIAL BRANCH OF NAHDLATUL ULAMA (PCINU) IN THE UNITED KINGDOM - Mochtar, Yusnan Hadi; Finny Fitria Febrin; Lusi Prihartanti (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2024)
As the research on moderate Islam is very state-centric, we need an alternative understanding by exploring the role of non-state actors in the issue. This article aims to provide the view by identifying the transnational religious actors from Indonesia, especially the Nahdlatul Ulama, in promoting moderate Islam on the global stage amid ongoing bad image of Indonesia and that religion circulated among global citizens because of terrorism. The research consists of two layers of analysis. First, we identify several cases of terrorism and radicalisation affecting Indonesians, and to the extent they also impacted Indonesia's image. Second, we explore the role of the Special Branch of Nahdlatul Ulama (PCINU) in the United Kingdom, that is actively constructing the message that Islam is not what people perceive. It is worth noting that PCINU has been in more than 30 countries, one of them is in the UK. The writers of this article chose the PCINU UK as representing the Western world in which people have a limited understanding of moderate Islam, moreover when there was the 9/11 attack affecting negatively on Islam. To analyze it further, we conducted in-depth interviews with PCINU UK and used library research by collecting data from journals, reports, and news related to the topic. It found that while terrorism has contributed negatively to Islam and Indonesia’s reputation, it is worth noting that PCINU in the UK plays a pivotal role in neutralizing the issue. NU is essential to bring another image of Indonesia and Islam that is modern and dynamic. Key words: transnational religious actor, multi-track diplomacy, nahdlatul ulama.